INTERROGATING RACE, CRIME, AND JUSTICE IN A TIME OF UNEASE AND RACIAL TENSION1. Issue 2 (27th April 2017) - PETERSON, RUTH D.
Abstract : This address has a twofold purpose. First, as the first African American to serve as president of the American Society of Criminology (ASC), I celebrate the contributions of scholars of color to the study of crime and criminal justice and to the ASC. I do so by pointing out the accomplishments of several African American scholars whose contributions are numerous and exemplary. I also emphasize that African Americans are joined in their efforts by scholars of multiple other colors, including, Latinos/as, Native Americans, and Asians. Second, in view of responses to apparent unrest and racial tension in U.S. society that is signaled by lethal violence between police and U.S. residents of color, I offer four recommendations regarding how we might proceed with our research, and report our findings, in ways that improve the likelihood of helping to inform societal debates and policy developments around crime and justice issues. In my conclusion, I encourage the ASC to 1) continue to grow the diversity of its membership and to integrate the research and findings of scholars of color into the mainstream of criminology; and 2) take further steps to conduct research and share findings with diverse audiences to ensure that post‐truth does not become normative regarding crime and justice issues.